2012
DOI: 10.1155/2012/504387
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Functional Electrical Stimulation to Assist Cycling in Four Adolescents with Spastic Cerebral Palsy

Abstract: Introduction. Adolescents with cerebral palsy (CP) often have difficulty participating in exercise at intensities necessary to improve cardiovascular fitness. Functional electrical stimulation- (FES-) assisted cycling is proposed as a form of exercise for adolescents with CP. The aims of this paper were to adapt methods and assess the feasibility of applying FES cycling technology in adolescents with CP, determine methods of performing cycling tests in adolescents with CP, and evaluate the immediate effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
41
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 43 publications
(66 reference statements)
0
41
0
1
Order By: Relevance
“…Functional electrical stimulation (FES) has been used to enhance the effect of locomotor training [15]. It was shown that in CP children FES assisted cycling or walking was tolerated well and resulted in increased muscle strength, balance improvement, normalization of biomechanical and innervation structure of locomotor act, increased cadence, power output, and heart rates [15,19].…”
Section: Introductionmentioning
confidence: 99%
“…Functional electrical stimulation (FES) has been used to enhance the effect of locomotor training [15]. It was shown that in CP children FES assisted cycling or walking was tolerated well and resulted in increased muscle strength, balance improvement, normalization of biomechanical and innervation structure of locomotor act, increased cadence, power output, and heart rates [15,19].…”
Section: Introductionmentioning
confidence: 99%
“…Integration of electric motor assist and FES has also been studied for this purpose [8], [9]. In addition to using the FES cycling as a mobility device, application of FES cycling to motor rehabilitation has been studied [10]- [12]. For the rehabilitation purpose, many studies have used stationary FES cycling system such Copyright c 2016 The Institute of Electronics, Information and Communication Engineers as bicycle ergometer combined with FES [13]- [20].…”
Section: Introductionmentioning
confidence: 99%
“…A course of FES during walking was shown to strengthen the paretic muscles, to improve peripheral circulation, to normalize the biomechanical and innervation structures of locomo tion, and to reduce the walking associated energy consumption. Harrington et al [53] assessed the feasi bility of applying FES cycling technology in adoles cents with CP and evaluated the immediate results of FES therapy performed during exercise on a cycling machine. FES assisted cycling was well tolerated and facilitated an increase in cycling cadence, power out put, and heart rate and a decrease in variability in cycling performance as compared with a control group without FES assistance during rehabilitation.…”
Section: Introductionmentioning
confidence: 99%